VD_FINDINFO Jug / 2015 / 313 vom 18. August 2015 - VD Tribunal cantonal (2015)
RÉVISIONDÉCISION, ADMISSION DE LA DEMANDE, IRRESPONSABILITÉ, CLASSEMENT DE LA PROCÉDURE | 319 al. 1 CPP (CH), 410 al. 1 let. a CPP (CH), 413 al. 2 CPP (CH)